MARITAL CONFLICTS BETWEEN THE MAIN CHARACTERS AND PARENTS-IN-LAW IN THE NOVEL GONE GIRL - Veraldy, Muhammad Abirzaim (LANTERN (Journal on English Language, Culture and Literature), 2017)
Gone Girl is a novel created by Gillian Flynn that is based on social problematique in the United States in the 21st century. The book depicts the marriage relationship that faces problems caused by the conflict that occurs their parents-in-law. The story refers to a theory from Serewicz which is In-Laws Relationship Theory. The writer uses this theory to analyze the story from sociological aspect. Library research is used to find important informations about in-laws relationship towards marriage. Qualitative research is used to analyze the novel deeper. The conclusion of the research is that there is a relation between in-laws relationship that can create a conflict in the marital which is sociologically examined.